Digital Archive Management Procedure Through Google Spreadsheet in The Staffing Unit of Politeknik Kesehatan Kemenkes Tasikmalaya - Putri Mutiara Agustin; Untung Eko Setyasari; Yudi Kurniadi (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Digital technology has become the main driver of change in various aspects of life, including digital archive management. Digital archive management is a major operational activity throughout university units, especially in the Staffing Unit of Politeknik Kesehatan Kemenkes Tasikmalaya. Archive management in this unit is currently in the transition period from conventional archiving to digital. As a result, the archiving process is still done double, first done conventionally and continued with the digital process. This is the background of the research to review archive management through Google Spreadsheet in the Staffing Unit of Politeknik Kesehatan Kemenkes Tasikmalaya. This research uses a qualitative method based on interviews with archivists in the Staffing Unit of Politeknik Kesehatan Kemenkes Tasikmalaya and also observation from September 2023 - January 2024. The result shows that the digital archiving process in this unit is carried out sequentially starting with moving documents, storing documents, indexing documents, controlling access and ending with document retention. So, digital archive management through google spreadsheet in the Staffing Unit of Politeknik Kesehatan Kemenkes Tasikmalaya has been carried out well. Thus, the digital archiving that has been carried out in this unit facilitates the process of finding the information needed and also streamlines the archivist's jobdesk.